2010
DOI: 10.1056/nejmoa0908679
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Induced Pluripotent Stem-Cell Models for Long-QT Syndrome

Abstract: We generated patient-specific pluripotent stem cells from members of a family affected by long-QT syndrome type 1 and induced them to differentiate into functional cardiac myocytes. The patient-derived cells recapitulated the electrophysiological features of the disorder. (Funded by the European Research Council and others.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
902
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,132 publications
(954 citation statements)
references
References 40 publications
28
902
3
5
Order By: Relevance
“…Patient-specific iPSderived cardiomyocytes (iPS-CMs) have been used to investigate inherited arrhythmia syndromes such as long QT syndrome (LQTS) and catecholeminergic polymorphic ventricular tachycardia (9,21,31,34). These proof of concept studies have recapitulated some characteristic features of human disease (8, 23).…”
Section: Ik1-enhanced Induced Pluripotent Stem Cell-derived Cardiomyomentioning
confidence: 99%
“…Patient-specific iPSderived cardiomyocytes (iPS-CMs) have been used to investigate inherited arrhythmia syndromes such as long QT syndrome (LQTS) and catecholeminergic polymorphic ventricular tachycardia (9,21,31,34). These proof of concept studies have recapitulated some characteristic features of human disease (8, 23).…”
Section: Ik1-enhanced Induced Pluripotent Stem Cell-derived Cardiomyomentioning
confidence: 99%
“…[57][58][59] These reports confirmed that patient-specific iPS cells can give rise to differentiated CMCs that possess the main functional and morphological aberration typical of the disease in vivo.…”
Section: Reprogramming Strategies: a Peek At Disease Mechanisms Whilementioning
confidence: 56%
“…the slow I Ks , and the rapid I Kr components of the delayed rectifier potassium currents, the sodium current I Na , and the L‐type calcium current I CaL ) varying widely even among wild‐type control hiPSC‐CMs 55, 56. Most notably, very different levels of I Ks have been described (ranging from ~ 0.3 to ~ 2.5 pA/pF 5, 57), variable observation leading to controversial conclusions: on the one hand, I Ks recapitulates physiological behaviour in playing a major role when repolarisation reserve is attenuated 58, 59; on the other, it seems to contribute to repolarisation in hiPSC‐CMs even in the absence of sympathetic stimulation 5, 36, 60, 61. The immature phenotype of all stem cell derivatives including hiPSC‐CMs is probably the reason for this variability but, independent of the cause, it is a limitation to extrapolating results obtained using hiPSC‐CMs to native – healthy and diseased – adult human CMs as discussed below.…”
Section: Pathological Phenotypes and New Mechanistic Insightsmentioning
confidence: 99%
“…Inherited cardiovascular disorders and in particular channelopathies have been among the first human diseases studied using iPSCs 5, 6, 7, 8. Indeed, although animal models have been and continue to be essential in advancing the understanding of cardiovascular disease 9, 10, 11, interspecies differences hamper translation of many results directly to humans.…”
mentioning
confidence: 99%